From Birds to Insects: The Diversity of Social Behavior - Liu Jiacheng (BIO Web of Conferences, 2024)
Social behavior in animals holds considerable importance in the fields of ecology and evolutionary biology, as it enhances our understanding of cooperation and competition among species. Nonetheless, there are notable variations in the expressions of social behavior across different taxa. This paper offers a comprehensive comparison of the social behaviors of birds and insects, analyzing characteristics such as gregarious behavior, cooperative breeding, and territoriality in birds, along with the social structure, nesting practices, larval care, food sharing, and group defense mechanisms in insects. The study aims to elucidate the similarities and differences in social behavior between these two groups, further investigating the roles of these behaviors in ecosystems and their evolutionary significance, thereby providing a novel perspective on the diversity of animal social behavior.